PENINGKATAN KETERAMPILAN MEMBACA PEMAHAMAN MENGGUNAKAN MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION DI SEKOLAH DASAR PONTIANAK - Kamariana, Kamariana, Siti Halidjah, Sugiyono; Halidjah, Siti; Sugiyono, Sugiyono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â AbstractThis research aimed to improve the skill of reading comprehension students with the using of cooperative integrated reading and composition model for grade V Elementary school 09 Pontianak Barat. The method used is descriptive method with class action research form and collaborative research. Subjects of the study were 34 students.This study was conducted during III cycle with each cycle one time meeting. This results of the ability of teachers to plan learning from cycle I is 3.54, the second cycle is 3.85, the third cycle is 3.90. The results of research from the implementation of learning from the cycle I is 3.79, the second cycle is 3.81, the third cycle is 3.93. The result of research reading comprehension essay from cycle I that is 66.80 cycle II that is 75.39, cycle III that is 76,95. So, using of cooperative integrated reading and composition model can improve the skill of reading comprehension students.Â Keywords: Cooperative Integrated Reading and Composition, improve, reading comprehensionÂ